Efficient salt elimination three-dimensional porous solar evaporator and preparation and application thereof

By adopting a three-dimensional porous structure of efficient salt discharge in solar evaporators and using Donnan to balance the repelling of salt ions, the problem of salt deposition on the surface of the evaporator is solved, and efficient and stable seawater desalination effect is achieved.

CN119746438AActive Publication Date: 2025-04-04SHANGHAI INST OF TECH

Patent Information

Application Number
CN202411752057.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-04-04
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

Existing solar evaporators are prone to salt deposition on the evaporator surface during long-term seawater desalination, which affects the structural stability and evaporation rate of the evaporator and requires regular cleaning and maintenance.

Method used

A high-efficiency salt discharge three-dimensional porous solar evaporator is used, which uses Donnan equilibrium to repel salt ions in the main water to avoid precipitation of salt crystals. The evaporator includes a porous foam copper skeleton after wet oxidation of the alkaline solution, a graphene oxide deposited layer and a water supply layer soaked by sodium polystyrene sulfonate.

Benefits of technology

While ensuring a high evaporation rate, it is achieved to reduce or avoid the precipitation of salt crystals on the surface of the evaporator, maintain long-term continuous evaporation stability, and overcome the defects in the prior art that salt crystals affect evaporation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746438A_ABST
    Figure CN119746438A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient salt elimination three-dimensional porous solar evaporator and preparation and application thereof. The evaporator is in an inverted cone shape. The evaporator comprises an efficient salt elimination porous foamy copper framework and a water supply layer attached to the outer side of the efficient salt elimination porous foamy copper framework; the efficient salt elimination porous foamy copper framework is a porous foamy copper framework which is sequentially subjected to alkaline solution wet oxidation treatment, graphene oxide deposition treatment and sodium polystyrenesulfonate soaking treatment. According to the efficient salt elimination three-dimensional porous solar evaporator, wet oxidation treatment of the alkaline solution brings super hydrophilicity to the evaporator, and evaporation enthalpy of water is reduced; the deposited graphene oxide can realize broadband light absorption, and provides a space for vapor diffusion and diffuse reflection of incident light in the porous skeleton; the evaporation area of water is enlarged through the inverted cone structure and the stacked framework; sO3 ionized from sodium polystyrenesulfonate is beneficial to repelling salt ions in main water, precipitation of salt crystals on the surface of the evaporator is reduced, and the application prospect is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photothermal evaporation materials, and in particular to a three-dimensional porous solar evaporator with high efficiency in salt removal, preparation thereof and application thereof, and in particular to a solar salt removal interface evaporator capable of achieving high efficiency in solar water evaporation while avoiding salt deposition, a preparation method thereof and application thereof. Background Art

[0002] As a new type of clean energy, solar energy has become an important part of people's daily production and life under the background of "dual carbon". In recent years, the use of solar energy to evaporate seawater to produce clean water has been considered one of the most promising green and sustainable solutions to the challenge of global water shortage.

[0003] Patent CN 118255412 A discloses a preparation method and application of a coconut fiber rope solar evaporator, which uses a carbon black photothermal film as a photothermal conversion material. Water is transported to the top photothermal layer through the axial micropores of the coconut fiber rope by capillary effect, and finally desalination of seawater is achieved; Patent CN 118165450 A discloses a solar water evaporation material including polydimethylsiloxane, photothermal conversion material and hydrophilic porous membrane, which uses a PAN porous membrane to achieve better water transport, and realizes the synergistic absorption and conversion of sunlight through MoS2 and carbon nanotubes; Patent CN 115432761 B discloses a natural solar evaporation material based on Salvinia and a preparation method thereof. By subjecting Salvinia to hydrophilic and oxidative modification, it has better water transport and light absorption capabilities, thereby achieving low-cost solar evaporation. However, these evaporators will inevitably have salt deposition on the surface of the evaporators during the long-term seawater desalination process, which will greatly affect the structural stability of the evaporator and reduce the evaporation rate. Regular cleaning and maintenance are required to ensure its operational stability, which will inevitably increase operating costs and affect economic benefits.

[0004] Therefore, a solar evaporator that can reduce salt crystallization on the evaporator surface while ensuring a high evaporation rate is of great practical significance. Summary of the invention

[0005] In view of the above-mentioned defects in the prior art, the present invention provides a solar evaporator that can reduce salt crystallization on the surface of the evaporator while ensuring a high evaporation rate. Specifically, the present invention provides a three-dimensional porous solar evaporator with high efficiency in salt rejection. The polyelectrolyte is deposited and the Donnan equilibrium is used to exclude salt ions from the main water to avoid the precipitation of salt crystals on the surface of the evaporator. The evaporation efficiency of 1.68 kg m was obtained under 1 sun. -2 h -1The evaporation rate can be increased and the evaporation stability can be maintained for a long time, which overcomes the defect of the existing solar evaporator that the surface salt crystallization affects the evaporation performance during long-term evaporation.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] A three-dimensional porous solar evaporator with high efficiency in salt removal, wherein the evaporator is in the shape of an inverted cone;

[0008] The evaporator comprises a highly efficient salt-removing porous foam copper skeleton and a water supply layer attached to the outside of the highly efficient salt-removing porous foam copper skeleton;

[0009] The highly efficient salt-removing porous copper foam skeleton is a porous copper foam skeleton that has been subjected to alkaline solution wet oxidation treatment, graphene oxide deposition treatment and sodium polystyrene sulfonate immersion treatment in sequence.

[0010] The efficient salt-removing three-dimensional porous solar evaporator of the present invention absorbs water through the water supply layer and disperses the water on the water supply layer to complete water transportation. At this time, the efficient salt-removing porous copper foam skeleton contacts water and can perform photothermal conversion to complete water evaporation. The efficient salt-removing porous copper foam skeleton is obtained after multiple treatments, wherein the alkaline solution wet oxidation treatment brings super hydrophilicity to the porous copper foam skeleton, improving the water supply efficiency; the deposited graphene oxide has high light absorption, high porosity, high thermal conductivity and chemical stability under various conditions, and cooperates with the light capture effect to further enhance light absorption; a large amount of SO3 ionized from sodium polystyrene sulfonate − Fixed on the surface of the skeleton, it repels ions in the brine into the main water through Donnan equilibrium, making the salt ion concentration entering the evaporator extremely low during water transportation, ultimately avoiding the precipitation of salt crystals on the surface of the evaporator or greatly reducing the amount of salt crystals precipitated on the surface of the evaporator, achieving efficient and long-term stable seawater desalination effect.

[0011] As the preferred technical solution:

[0012] In the above-mentioned efficient salt-removing three-dimensional porous solar evaporator, the water supply layer is a dust-free paper layer soaked in sodium polystyrene sulfonate. The dust-free paper is soaked in sodium polystyrene sulfonate, that is, the sodium polystyrene sulfonate immersed in the dust-free paper ionizes a large amount of SO3 − Fixed on the surface of the skeleton, the ions in the brine can be excluded from the main water through the Donnan equilibrium (reducing the amount of ions in the water absorbed by the water supply layer), so that the salt ion concentration entering the evaporator during water transportation is extremely low, thereby reducing the amount of salt crystals precipitated on the surface of the evaporator.

[0013] In the above-mentioned efficient salt-removing three-dimensional porous solar evaporator, the alkaline solution is a mixed solution of NaOH and NaClO2.

[0014] In the highly efficient salt-removing three-dimensional porous solar evaporator as described above, the apex angle of the inverted cone is 30° to 90°.

[0015] The present invention also provides a method for preparing the above-mentioned efficient salt-removing three-dimensional porous solar evaporator, comprising the following steps:

[0016] S1: Cut the sheet-like porous copper foam into a fan shape and bend it into an inverted cone shape;

[0017] S2: pre-treating the porous copper foam: placing the porous copper foam obtained in step S1 in dilute hydrochloric acid for ultrasonic cleaning to remove oxides and impurities on the surface of the skeleton, and then washing with deionized water and drying with nitrogen;

[0018] S3: Super-hydrophilic treatment: The porous copper foam skeleton obtained in step S2 is placed in a mixed solution of NaOH and NaClO2 for wet oxidation to form a black super-hydrophilic structure on the surface of the skeleton, and then washed with deionized water and dried naturally;

[0019] S4: Depositing graphene oxide: placing the super hydrophilic porous copper foam skeleton (SHiCF) obtained in step S3 in a graphene oxide (GO) dispersion for physical deposition and naturally drying;

[0020] S5: introducing a salt-repelling structure: placing the super-hydrophilic porous copper foam skeleton (SHiCF-GO) deposited with graphene oxide obtained in step S4 in a sodium polystyrene sulfonate (PSS) solution for immersion treatment and naturally drying;

[0021] S6: Cut the dust-free paper into sectors of the same size as in step S1 and place them in a sodium polystyrene sulfonate (PSS) solution for immersion and allow to dry naturally;

[0022] S7: Wrap the dust-free paper obtained in step S6 tightly around the outside of the conical sample (SHiCF-GO-PSS) obtained in step S5 to obtain a high-efficiency salt-removing three-dimensional porous solar evaporator.

[0023] As the preferred technical solution:

[0024] The method as described above further comprises:

[0025] S8: Fixing the efficient salt-removing three-dimensional porous solar evaporator on the thermal insulation material, and the tip of the efficient salt-removing three-dimensional porous solar evaporator penetrates the thermal insulation material.

[0026] In the method as described above, the thermal insulation material is polystyrene foam.

[0027] In the method described above, the PPI of the sheet-like porous copper foam in step S1 is 100-130, and the porosity is greater than 90%;

[0028] In step S2, the concentration of dilute hydrochloric acid is 3-10wt%, the ultrasonic cleaning time is 5-10min, and the temperature is 20-30°C;

[0029] The molar mass concentration of NaOH in the alkaline solution in step S3 is 1-3 mol / L, and the molar mass concentration of NaClO2 is 1-3 mol / L;

[0030] The wet oxidation in step S3 is performed at a temperature of 70-80°C for 1-2 hours;

[0031] In step S4, the graphene oxide concentration of the graphene oxide (GO) dispersion is 1.5-2.5 mg / mL, and the physical deposition time is 1-1.5 h;

[0032] In step S5, the concentration of the sodium polystyrene sulfonate solution is 0.1-0.8 g / L, and the soaking time is 1-2 h;

[0033] The concentration of the sodium polystyrene sulfonate solution in step S6 is 0.1-0.8 g / L, and the soaking time is 1-2 h.

[0034] In addition, the present invention also provides the application of the above-mentioned efficient salt-removing three-dimensional porous solar evaporator in seawater desalination.

[0035] The above technical solution is only a feasible technical solution of the present invention, and the protection scope of the present invention is not limited thereto. Those skilled in the art can reasonably adjust the specific design according to actual needs.

[0036] Invention mechanism:

[0037] The present invention uses a simple and easily available foam copper skeleton as a substrate, and chemically etches and physically deposits it to give it super-hydrophilicity and broadband light absorption performance. The cross-stacked skeleton structure of the foam copper with high porosity gives it the characteristics of high permeability, high specific surface area and capillary force. The black flaky super-hydrophilic nanostructure layer formed on the surface of the foam copper skeleton provides a site for the climbing of water molecules. At the same time, because it contains a large number of hydrophilic oxygen-containing functional groups, it reduces the evaporation enthalpy of water, giving the skeleton super-hydrophilicity. The GO deposited on the oxidized foam copper skeleton has high light absorption, high porosity, high thermal conductivity and chemical stability under various conditions. The cross-stacked skeleton of the foam copper provides structural support for GO, and GO cooperates with the light capture effect to further enhance light absorption. The closely arranged π electron energy levels in carbon-based nanomaterials such as GO can achieve efficient absorption of sunlight of different wavelengths. At the same time, the deposited GO of appropriate concentration does not block the pores, providing space for vapor diffusion and diffuse reflection of incident light inside the porous skeleton. A large amount of SO3 ionized by PSS −It is fixed on the surface of the skeleton and excludes the ions in the salt water from the main water through Donnan equilibrium (reducing the amount of ions in the water absorbed by the water supply layer), so that the salt ion concentration entering the evaporator during the water transportation process is extremely low, and finally avoids the precipitation of salt crystals on the surface of the evaporator or greatly reduces the precipitation of salt crystals on the surface of the evaporator, achieving continuous and efficient interfacial evaporation, and achieving efficient and long-term stable seawater desalination effect. The macroscopic 3D inverted cone structure and stacked foam copper skeletons expand the evaporation area of ​​water, and the good thermal conductivity quickly converts the absorbed heat into the evaporation enthalpy of water while achieving good thermal positioning.

[0038] The above invention has the following advantages or beneficial effects:

[0039] (1) The high-efficiency salt-removing three-dimensional porous solar evaporator of the present invention uses raw materials such as foam copper and GO, which are easy to obtain and low in cost;

[0040] (2) The high-efficiency salt-removing three-dimensional porous solar evaporator of the present invention has a high thermal conductivity of the foam copper skeleton, which can conduct heat better and faster, making the temperature distribution more uniform and achieving good thermal positioning. At the same time, its porous structure provides a place for continuous diffuse reflection and absorption of sunlight and diffusion of vapor. Its stacked skeleton greatly increases the evaporation area of ​​water, achieving more efficient solar evaporation;

[0041] (3) The high-efficiency salt-removing three-dimensional porous solar evaporator of the present invention has a reasonable structural design and a structural arrangement that reduces heat loss during evaporation. The polyethylene foam with low thermal conductivity and the air layer separate the water body from the light-to-heat conversion layer, effectively solving the problem of large amounts of heat loss caused by the evaporation device dissipating heat to the water body.

[0042] (4) The preparation method of the high-efficiency salt-removing three-dimensional porous solar evaporator of the present invention is simple to operate and pollution-free. The foam copper skeleton is given good hydrophilicity and light absorption properties by simple chemical modification and physical deposition, and a good salt removal effect is achieved in the water transport stage by immersing it in PSS and utilizing the Donnan equilibrium. The long-term continuous and high-efficiency evaporation stability of the solar evaporator is greatly improved, and the cost of cleaning and maintenance of the evaporator in the later stage is saved. It has good prospects for large-scale preparation and commercial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The present invention and its features, appearance and advantages will become more apparent by reading the detailed description of non-limiting embodiments with reference to the following drawings. The same reference numerals indicate the same parts in all the drawings. The drawings are not drawn to scale, and emphasis is placed on illustrating the subject matter of the present invention.

[0044] Figure 1 This is a schematic diagram of the structure of a three-dimensional porous solar evaporator with high efficiency in salt removal;

[0045] Figure 2 A flow chart of a method for preparing a three-dimensional porous solar evaporator with high efficiency in salt removal;

[0046] Figure 3 This is the SEM image of the super-hydrophilic structure on the three-dimensional porous solar evaporator with high efficiency of salt removal;

[0047] Figure 4 SEM images of different concentrations of GO (graphene oxide) deposited on a three-dimensional porous solar evaporator for efficient salt removal. Figure 4 (a) corresponds to a GO concentration of 1.5 mg / L, Figure 4 (b) corresponds to a GO concentration of 2.5 mg / L;

[0048] Figure 5 This is a graph showing the evaporation rate changes of the present evaporator and the comparative example in simulated seawater (1.5wt% NaCl solution) for 10 consecutive days. DETAILED DESCRIPTION

[0049] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but they are not intended to limit the present invention.

[0050] Example 1

[0051] A method for preparing a highly efficient salt-removing three-dimensional porous solar evaporator, the steps of which are as follows: Figure 2 As shown, specifically:

[0052] S1: Cut the sheet-like porous copper foam into a fan shape and bend it into an inverted cone shape;

[0053] Specifically, a copper foam with a PPI of 130, a porosity of 96.5%, and a thickness of 2 mm was selected, and a sector with an angle of 137.6° and a radius of 71.86 mm was cut and bent into an inverted cone with a cone top angle of 45° and a diameter of 55 mm.

[0054] S2: The porous copper foam obtained in step S1 is placed in dilute hydrochloric acid for ultrasonic cleaning to remove oxides and impurities on the surface of the skeleton, and then washed with deionized water and dried with nitrogen;

[0055] Specifically, the porous copper foam obtained in step S1 is placed in a dilute hydrochloric acid solution with a concentration of 10 wt % and cleaned by ultrasonic vibration at 20° C. for 5 min, and then the sample is cleaned with deionized water and blown dry with nitrogen.

[0056] S3: placing the porous copper foam skeleton obtained in step S2 in a mixed alkaline solution of NaOH and NaClO2 for wet oxidation to form a black super-hydrophilic structure on the surface of the skeleton, such as Figure 3 As shown, it was then washed with deionized water and dried naturally;

[0057] Specifically, firstly, NaOH and NaClO2 solutions are mixed to obtain a mixed alkaline solution, wherein the concentrations of NaOH and NaClO2 in the mixed alkaline solution are both 2 mol / L. Then, the porous copper foam skeleton obtained in step S2 is placed in the mixed alkaline solution and wet-oxidized in a constant temperature box at 75° C. for 1 h to form a black super-hydrophilic structure on the surface of the copper foam skeleton, and then washed with deionized water and dried naturally.

[0058] S4: placing the super hydrophilic porous copper foam skeleton (SHiCF) obtained in step S3 in a graphene oxide (GO) suspension for physical deposition and drying naturally;

[0059] Specifically, a GO suspension was first prepared, GO powder was added to deionized water and ultrasonically vibrated for 10 min to form a uniform suspension with a concentration of 2.5 mg / L, and the super hydrophilic porous copper foam skeleton (SHiCF) obtained in step S3 was placed in the graphene oxide (GO) suspension for physical deposition for 1 h, and then naturally dried.

[0060] S5: placing the super hydrophilic porous copper foam skeleton (SHiCF-GO) deposited with GO obtained in step S4 in a sodium polystyrene sulfonate (PSS) solution for immersion treatment and naturally drying;

[0061] Specifically, the PSS solution is first dissolved in deionized water to form a 0.1 g / L PSS solution. Then, the super hydrophilic porous copper foam skeleton (SHiCF-GO) deposited with GO obtained in step S4 is immersed in a sodium polystyrene sulfonate (PSS) solution for 1 hour and dried naturally.

[0062] S6: Cut the dust-free paper into sectors of the same size as in step S1 and place them in a sodium polystyrene sulfonate (PSS) solution for immersion and allow to dry naturally;

[0063] Specifically, the dust-free paper was cut into a sector with an angle of 137.6° and a radius of 71.86 mm, immersed in a sodium polystyrene sulfonate (PSS) solution for 1 h and dried naturally;

[0064] S7: Wrap the dust-free paper obtained in step S6 tightly around the outside of the conical sample (SHiCF-GO-PSS) obtained in step S5 and fix the obtained evaporator on the disc-shaped polystyrene foam. The evaporator has a structure as follows: Figure 1 shown.

[0065] Specifically, the dust-free paper obtained in step S6 is first tightly wrapped around the outside of the conical sample (SHiCF-GO-PSS) obtained in step S5 to ensure sufficient water transport, and then a through hole with a diameter of 15 mm is cut in the center of a circular polystyrene foam with a diameter of 60 mm and a thickness of 2.5 cm, so that the lower part of the dust-free paper can pass through the through hole and contact with the main water to achieve water transport.

[0066] Example 2

[0067] A method for preparing a high-efficiency salt-removing three-dimensional porous solar evaporator comprises the following steps:

[0068] S1: Cut the sheet-like porous copper foam into a fan shape and bend it into an inverted cone shape;

[0069] Specifically, a copper foam with a PPI of 115, a porosity of 93.5%, and a thickness of 2 mm was selected, and a sector with an angle of 137.6° and a radius of 78.39 mm was cut and bent into an inverted cone with a cone apex angle of 60° and a diameter of 60 mm.

[0070] S2: The porous copper foam obtained in step S1 is placed in dilute hydrochloric acid for ultrasonic cleaning to remove oxides and impurities on the surface of the skeleton, and then washed with deionized water and dried with nitrogen;

[0071] Specifically, the porous copper foam obtained in step S1 is placed in a dilute hydrochloric acid solution with a concentration of 8 wt % and cleaned by ultrasonic vibration at 20° C. for 5 min, and then the sample is cleaned with deionized water and dried.

[0072] S3: placing the porous copper foam skeleton obtained in step S2 in a mixed alkaline solution of NaOH and NaClO2 for wet oxidation to form a black super-hydrophilic structure on the surface of the skeleton. Then, washing with deionized water and drying naturally;

[0073] Specifically, firstly, NaOH and NaClO2 solutions are mixed to obtain a mixed alkaline solution, wherein the concentrations of NaOH and NaClO2 in the mixed alkaline solution are both 3 mol / L. Then, the porous copper foam skeleton obtained in step S2 is placed in the mixed alkaline solution and wet-oxidized at 80° C. for 1 h in a constant temperature box to form a black super-hydrophilic structure on the surface of the copper foam skeleton, and then washed with deionized water and dried naturally.

[0074] S4: placing the super hydrophilic porous copper foam skeleton (SHiCF) obtained in step S3 in a graphene oxide (GO) suspension for physical deposition and naturally drying;

[0075] Specifically, a GO suspension was first prepared, GO powder was added to deionized water and ultrasonically vibrated to form a uniform suspension with a concentration of 1.5 mg / mL, and the super hydrophilic porous copper foam skeleton (SHiCF) obtained in step S3 was placed in the graphene oxide (GO) suspension for physical deposition for 1 hour, and then naturally dried.

[0076] S5: placing the super hydrophilic porous copper foam skeleton (SHiCF-GO) deposited with GO obtained in step S4 in a sodium polystyrene sulfonate (PSS) solution for immersion treatment and naturally drying;

[0077] Specifically, the PSS solution is first dissolved in deionized water to form a 0.5 g / L PSS solution. Then, the super hydrophilic porous copper foam skeleton (SHiCF-GO) deposited with GO obtained in step S4 is immersed in a sodium polystyrene sulfonate (PSS) solution for 1 hour and dried naturally.

[0078] S6: Cut the dust-free paper into sectors of the same size as in step S1 and place them in a sodium polystyrene sulfonate (PSS) solution for immersion and allow to dry naturally;

[0079] Specifically, the dust-free paper was cut into a sector with an angle of 137.6° and a radius of 78.39 mm, placed in a sodium polystyrene sulfonate (PSS) solution for immersion for 1 h and naturally dried;

[0080] S7: Wrap the dust-free paper obtained in step S6 tightly around the outside of the conical sample (SHiCF-GO-PSS) obtained in step S5 and fix the obtained evaporator on the disc-shaped polystyrene foam.

[0081] Specifically, the dust-free paper obtained in step S6 is first tightly wrapped around the outside of the conical sample (SHiCF-GO-PSS) obtained in step S5 to ensure sufficient water transport. Then, a through hole with a diameter of 15 mm is cut in the center of a circular polystyrene foam with a diameter of 60 mm and a thickness of 2.5 cm, so that the lower part of the dust-free paper can pass through the through hole and contact with the main water to achieve water transport.

[0082] Example 3

[0083] A method for preparing a high-efficiency salt-removing three-dimensional porous solar evaporator is basically the same as Example 1, except that: S1, the selected foam copper has a PPI of 125, a porosity of 95.5%, a thickness of 2 mm, a cone evaporator with a cone apex angle of 50° and a caliber of 55 mm; S2, the concentration of hydrochloric acid for removing impurities on the surface of the foam copper is 5wt%; S3, when wet oxidation is performed, the molar mass concentration of NaOH in the alkaline solution is 1.5 mol / L, and the molar mass concentration of NaClO2 is 1.5 mol / L; S4, when GO deposition is performed, the concentration of the GO suspension used is 2 mg / mL, and the deposition time is 1.5 h; S5, when PSS solution immersion treatment is performed, the concentration of the PSS solution is 0.4 g / L, and the immersion time is 1.5 h.

[0084] Example 4

[0085] A method for preparing a high-efficiency salt-removing three-dimensional porous solar evaporator is basically the same as Example 1, except that: S1, the selected foam copper has a PPI of 120, a porosity of 94.5%, a thickness of 2 mm, a cone evaporator with a cone vertex angle of 55° and a caliber of 55 mm; S2, the concentration of hydrochloric acid for removing impurities on the surface of the foam copper is 7wt%; S3, when wet oxidation is performed, the molar mass concentration of NaOH in the alkaline solution is 2.5 mol / L, and the molar mass concentration of NaClO2 is 2.5 mol / L; S4, when GO deposition is performed, the concentration of the GO suspension used is 1.8 mg / mL, and the deposition time is 1 h; S5, when PSS solution immersion treatment is performed, the concentration of the PSS solution is 0.6 g / L, and the immersion time is 1 h.

[0086] Comparative Example 1

[0087] A method for preparing a three-dimensional porous solar evaporator is basically the same as Example 1, except that there are no steps S5 to S7, and after obtaining a super hydrophilic porous copper foam skeleton (SHiCF-GO) deposited with GO, the dust-free paper is cut into a fan shape with an angle of 137.6° and a radius of 71.86 mm, and then the dust-free paper is tightly wrapped around the outside of the super hydrophilic porous copper foam skeleton (SHiCF-GO) deposited with GO and fixed on a disc-shaped polystyrene foam (a through hole with a diameter of 15 mm is cut in the center of the circular polystyrene foam with a diameter of 60 mm and a thickness of 2.5 cm, so that the lower part of the dust-free paper can pass through the through hole and contact with the main water to achieve water transport).

[0088] Comparative Example 2

[0089] A method for preparing a three-dimensional porous solar evaporator is basically the same as that of Example 1, except that there is no step S6, i.e., the dust-free paper is not placed in a sodium polystyrene sulfonate (PSS) solution, and step S7 is: cutting the dust-free paper into a fan shape with an angle of 137.6° and a radius of 71.86 mm, and then tightly wrapping the dust-free paper around the outside of the conical sample (SHiCF-GO-PSS) obtained in step S5 and fixing it on a disc-shaped polystyrene foam (a through hole with a diameter of 15 mm is cut in the center of the circular polystyrene foam with a diameter of 60 mm and a thickness of 2.5 cm, so that the lower part of the dust-free paper can pass through the through hole and contact with the main water to achieve water transport).

[0090] The evaporators prepared in Example 1 and Comparative Examples 1-2 were subjected to a simulated seawater (1.5wt% NaCl solution) evaporation test for 10 consecutive days. The specific test operation was as follows: an electronic balance was used to monitor the mass change of the main water during the evaporation process. The evaporation was performed for 9 hours per day for 10 consecutive days, and the evaporation rate changes of the evaporator were compared.

[0091] The evaporation rate of the evaporator prepared in Example 1 and Comparative Examples 1-2 in simulated seawater for 10 consecutive days is shown in the figure below: Figure 5 As shown, Figure 5 SHiCF-GO-PSS+air-laid paper-PSS corresponds to Example 1, SHiCF-GO +air-laid paper corresponds to Example 1, SHiCF-GO-PSS+air-laid paper corresponds to Example 2, Figure 5 It can be seen that the mass of the main water in Example 1 is reduced the least. By observing the surfaces of the evaporators prepared in Example 1 and Comparative Examples 1-2, it can be found that no crystals are precipitated on the surface of the evaporator in Example 1, some crystals are precipitated on the surface of the evaporator in Comparative Example 1, and a small amount of crystals are precipitated on the surface of the evaporator in Comparative Example 2. In summary, the presence of PSS in the evaporator can greatly reduce the amount of salt crystals precipitated on the surface of the evaporator, realize continuous and efficient interfacial evaporation, and achieve efficient and long-term stable seawater desalination effect.

[0092] Those skilled in the art should understand that those skilled in the art can implement variations by combining the prior art and the above embodiments, which will not be described in detail here. Such variations do not affect the essential content of the present invention, and will not be described in detail here.

[0093] The above describes the preferred embodiments of the present invention. It should be understood that the present invention is not limited to the above-mentioned specific embodiments, and the devices and structures that are not described in detail should be understood to be implemented in a common manner in the art; any technician familiar with the art can use the above-disclosed methods and technical contents to make many possible changes and modifications to the technical solutions of the present invention without departing from the scope of the technical solutions of the present invention, or modify them into equivalent embodiments of equivalent changes, which does not affect the essential content of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solutions of the present invention are still within the scope of protection of the technical solutions of the present invention.

Claims

1. A highly efficient three-dimensional porous solar evaporator for salt removal, characterized by: The evaporator is in an inverted cone shape; The evaporator comprises a highly efficient salt-removing porous foam copper skeleton and a water supply layer attached to the outside of the highly efficient salt-removing porous foam copper skeleton; The highly efficient salt-removing porous copper foam skeleton is a porous copper foam skeleton that is sequentially treated with alkaline solution wet oxidation, graphene oxide deposition and sodium polystyrene sulfonate immersion.

2. The high-efficiency salt-removing three-dimensional porous solar evaporator according to claim 1 is characterized in that: The water supply layer is a dust-free paper layer soaked in sodium polystyrene sulfonate.

3. The high-efficiency salt-removing three-dimensional porous solar evaporator according to claim 2 is characterized in that: The alkaline solution is a mixed solution of NaOH and NaClO2.

4. The high-efficiency salt-removing three-dimensional porous solar evaporator according to claim 1 is characterized in that: The apex angle of the inverted cone is 30° to 90°.

5. A method for preparing a high-efficiency salt-removing three-dimensional porous solar evaporator as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S1: Cut the sheet-like porous copper foam into a fan shape and bend it into an inverted cone shape; S2: pre-treating the porous copper foam: placing the porous copper foam obtained in step S1 in dilute hydrochloric acid for ultrasonic cleaning, then washing with deionized water and drying with nitrogen; S3: Super-hydrophilic treatment: The porous copper foam skeleton obtained in step S2 is placed in a mixed solution of NaOH and NaClO2 for wet oxidation to form a black super-hydrophilic structure on the surface of the skeleton, and then washed with deionized water and dried naturally; S4: Depositing graphene oxide: placing the super-hydrophilic porous copper foam skeleton obtained in step S3 in a graphene oxide dispersion for physical deposition and naturally drying; S5: introducing a salt-repelling structure: placing the super-hydrophilic porous copper foam skeleton deposited with graphene oxide obtained in step S4 in a sodium polystyrene sulfonate solution for immersion treatment and naturally drying; S6: cutting the dust-free paper into sectors of the same size as in step S1 and placing them in a sodium polystyrene sulfonate solution for immersion and naturally drying; S7: Wrap the dust-free paper obtained in step S6 tightly around the outside of the conical sample obtained in step S5 to obtain a high-efficiency salt-removing three-dimensional porous solar evaporator.

6. The method according to claim 5, characterized in that Also includes: S8: Fixing the efficient salt-removing three-dimensional porous solar evaporator on the thermal insulation material, and the tip of the efficient salt-removing three-dimensional porous solar evaporator penetrates the thermal insulation material.

7. The method according to claim 6, characterized in that The thermal insulation material is polystyrene foam.

8. The method according to claim 5, characterized in that The PPI of the sheet-like porous copper foam in step S1 is 100-130, and the porosity is more than 90%; In step S2, the concentration of dilute hydrochloric acid is 3-10wt%, the ultrasonic cleaning time is 5-10min, and the temperature is 20-30°C; The molar mass concentration of NaOH in the alkaline solution in step S3 is 1-3 mol / L, and the molar mass concentration of NaClO2 is 1-3 mol / L; The wet oxidation in step S3 is performed at a temperature of 70-80°C for 1-2 hours; The graphene oxide concentration of the graphene oxide dispersion in step S4 is 1.5-2.5 mg / mL, and the physical deposition time is 1-1.5 h; In step S5, the concentration of the sodium polystyrene sulfonate solution is 0.1-0.8 g / L, and the soaking time is 1-2 h; The concentration of the sodium polystyrene sulfonate solution in step S6 is 0.1-0.8 g / L, and the soaking time is 1-2 h.

9. Application of a high-efficiency salt-removing three-dimensional porous solar evaporator as claimed in any one of claims 1 to 4 in seawater desalination.

Citation Information

Patent Citations

  • Method for modifying waterborne wood coating by hybridizing one-dimensional nano-cellulose by virtue of two-dimensional graphene oxide

    CN105754470A

  • Modified graphene and preparation method thereof

    CN106829942A

  • Preparation method of photothermal conversion porous structure and solar evaporation device

    CN113860354A

  • Efficient salt-repellent solar evaporator for heavy salt water treatment and preparation method of efficient salt-repellent solar evaporator

    CN116553667A

  • Photo-thermal evaporator based on nickel-cobalt bimetallic oxide

    CN117361672A

Cited By

  • A polymer foam with high photothermal conversion efficiency and its preparation method

    CN120944290B